Agency, Social Status and Performing Marriage in Postcolonial Societies. (November 2019) - Dery, Isaac; Bawa, Sylvia
This article examines contextually-grounded perspectives on the socio-political significance of marriage in contemporary Ghanaian society. Drawing on qualitative interviews among men and women in northwestern Ghana, this article argues that, beyond historicizing the institution of monogamous marriage, women's agency in desiring, and navigating marriages are performatively agentic and tied to attaining a myriad of socio-cultural, economic and political capital. Situated within the constrained articulations of participants, our findings alert us to complex negotiations and manoeuvres through which men and women aspire for specific forms of masculinities and femininities within the larger gender hierarchies.